(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2023)
This article talks about the problems of implementing the modern requirements for the formation of the spiritual and moral culture of a person, its connection with the development of the social system, its emergence as a result of cultural and humanitarian activities, in the process of material and spiritual activities of people.